Digital (Electronic) Democracy in Russia: Issues of Further Development - Albina Lolaeva; Margarita Lebedeva; Natalya Matveeva; Irina Nesmeianova; Victor Ocheredko; Svetlana Platonova (Jurnal Cita Hukum, 2022)
The study addresses the issues of further development of digital (electronic) democracy in Russia. Digitalization has penetrated into all spheres of public life. The sphere of public administration is no exception. The authors provide various scientific interpretations of democracy as a form of exercise of state power, in which the individual is given maximum freedom to exercise their rights and freedoms, as well as the ability to participate in the public life of the state. The study employs general scientific and private scientific methods. The authors conclude that the development of information and communication technologies will lead to a complete reorganization of public administration systems. The advancement of scientific and technological progress makes it possible to implement the power of the people in various digital (electronic) forms. The construction of an electronic state is in full swing. To develop a highly advanced, sovereign, prosperous state, it is necessary to safely introduce the tools of digital (electronic) democracy into the political life of the country